PENGARUH PLIOMETRIC TERHADAP PENINGKATAN DAYA TAHAN VO2Max PADA ATLET KABADDI SUL SEL - Reza Mahyuddin; Akbar Sudirman; Hasbi Asyhari (JURNAL PENDIDIKAN GLASSER, 2021)
This study used an experimental design for athletes from Kabaddi South Sulawesi with the aim of knowing how much influence the 'pliometric' exercise had on the increase in VO2Max in Kabaddi athletes in South Sulawesi province. Kabaddi is a new sport that has entered Indonesia and needs achievement development. Therefore, to improve the performance of Kabaddi athletes, programmed plyometric training is required. In taking the sample, it was done by using purposive sandom sampling technique. By using the SPSS 16 analysis technique with a significant level α = 0.05.